Spatial effects of shifting prisms on properties of posterior parietal cortex neurons - Karkhanis, Anushree N (J Physiol, 2014)
The posterior parietal cortex contains neurons that respond to visual stimulation and motor behaviour. The objective of the current study was to test short-term adaptation in neurons in macaque area 7a and the dorsal prelunate during visually guided reaching using Fresnel prisms that displaced the visual field. The visual perturbation shifted the eye position and created a mismatch between perceived and actual reach location. Two non-human primates were trained to reach to visual targets before, during and after prism exposure while fixating the reach target in different locations. They were required to reach to the physical location of the reach target and not the perceived, displaced location. While behavioural adaptation to the prisms occurred within a few trials, the majority of neurons responded to the distortion either with substantial changes in spatial eye position tuning or changes in overall firing rate. These changes persisted even after prism removal. The spatial changes were not correlated with the direction of induced prism shift. The transformation of gain fields between conditions was estimated by calculating the translation and rotation in Euler angles. Rotations and translations of the horizontal and vertical spatial components occurred in a systematic manner for the population of neurons suggesting that the posterior parietal cortex retains a constant representation of the visual field remapping between experimental conditions.